USING JOURNAL ENTRIES AND ASSIGNED WRITING TO PROMOTE STUDENTS’ CRITICAL THINKING - Arifin, Syaadiah; Ilyas, Hamzah Fuadi; Sukmawidjaya, Maula (VELES Voices of English Language Education Society, 2020)
This research aims to determine the ability of journal entries and assigned writing to foster students? critical thinking. A total of six components, namely, interpretation, analysis, evaluation, inference, explanation, and self-regulation were used to carry out this study. Data were obtained from a total of twelve (12) students majoring in English Education from one of the universities in Jakarta by using semi-structured interview and text-analysis. Journal entries submitted by the students as a course prerequisite were evaluated and analyzed by two raters. The result showed that many students lack important critical thinking skills required for a successful study, and to acquire good employment after graduating from college. In addition, the use of journal entries and assigned writing has the ability to promote this skill level to varying degrees.